2017
DOI: 10.3233/mgc-170229
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical identification of volatile fraction, essential oil and screening of antioxidant, antibacterial, allelopathic and insecticidal potential from Artemisia herba-alba leaves

Abstract: In the present paper, the essential oil and the volatiles emitted in vivo by leaves of A. herba alba, which grows wild in center of Tunisia, were analyzed by GC-MS and SPME, respectively. The essential oil was characterized by the predominance of oxygenated monoterpenes (93.3%) with α-thujone as the major compound (45.5%) followed by β-thujone (11.4%), trans-sabinyl acetate (10.1%) and 1,8-cineole (7.4%). The SPME analyses showed that oxygenated monoterpenes were the most representative compounds (64.9%). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…aureus , E. coli , and B. cereus [23,32,33]. Moreover, several studies showed a great potential of A. herba-alba EO oil as an antibacterial agent against Klebsiella pneumoniae , Listeria monocytogenes , Vibrio colerae , and S. Typhimurium [34,35,36]. Our results showed variable antimicrobial and antifungal activity of the essential oil, being the inhibition zones in the range of 10–24 mm.…”
Section: Discussionmentioning
confidence: 67%
“…aureus , E. coli , and B. cereus [23,32,33]. Moreover, several studies showed a great potential of A. herba-alba EO oil as an antibacterial agent against Klebsiella pneumoniae , Listeria monocytogenes , Vibrio colerae , and S. Typhimurium [34,35,36]. Our results showed variable antimicrobial and antifungal activity of the essential oil, being the inhibition zones in the range of 10–24 mm.…”
Section: Discussionmentioning
confidence: 67%
“…The following results have been identified as not sensitive for diameters of ≤ 8mm, sensitive for diameters of 8-14mm, very sensitive for diameters of 14-20mm, and extremely sensitive for diameters of ≥20mm (Bellili et al, 2017). L. monocytogenes ATCC 7644 and S. aureus ATCC 29213 were both significantly (p ≤ 0.05) sensitive to methanolic extract, with L. monocytogenes ATCC 7644 showing the greatest inhibition activity (13.00 mm).…”
Section: Distilled Watermentioning
confidence: 99%
“…The pronounced antioxidant activity may be due to the phenolic constituents. A. campestris oil showed maximal DPPH activity at dose of 2 mg/mL [ 110 ], however, A. herba - alba oil showed strong DPPH activity (IC 50 6 μg/mL) than ABTS assay (IC 50 40 μg/mL) [ 72 ]. In another study, IC 50 values of A. turanica oil reported were 7.00 mg/mL, 9.69 μg and 14.63 μg, in DPPH, nitric oxide and superoxide anion radicals, respectively.…”
Section: Antioxidant Activitymentioning
confidence: 99%